Single, but not mixed dietary fibers suppress body weight gain and adiposity in high fat-fed mice - Shallangwa, Swang M.; Ross, Alexander W.; Morgan, Peter J. (Frontiers in Microbiology, 2025)
Dietary fiber can suppress excess adipose tissue and weight gain in rodents and humans when fed high fat diets. The gut microbiome is thought to have a key role, although exactly how remains unclear. In a tightly controlled murine study, we explored how different types of dietary fiber and doses affect the gut microbiota and gut epithelial gene expression. We show that 10% pectin and 10% FOS suppress high fat diet (HFD)-induced weight gain, effects not seen at 2% doses. Furthermore, 2 and 10% mixtures of dietary fiber were also without effect. Each fiber treatment stimulated a distinct gut microbiota profile at the family and operational taxonomic unit (OTU) level. Mechanistically it is likely that the single 10% fiber dose shifted selected bacteria above some threshold abundance, required to suppress body weight, which was not achieved by the 10% Mix, composed of 4 fibers each at 2.5%. Plasma levels of the gut hormone PYY were elevated by 10% pectin and FOS, but not 10% mixed fibers, and similarly RNA seq revealed some distinct effects of the 10% single fibers on gut epithelial gene expression. These data show how the ability of dietary fiber to suppress HFD-induced weight gain is dependent upon both fiber type and dose. It also shows that the microbial response to dietary fiber is distinct and that there is not a single microbial response associated with the inhibition of adiposity and weight gain. PYY seems key to the latter response, although the role of other factors such as Reg3γ and CCK needs to be explored.